Study of shape effect of Pd promoted Ga2O3 nanocatalysts for methanol synthesis and utilization - Zhou, X (2013)
The area of methanol synthesis and utilization has been attracting research interests due to its positive impact on the environment and also from energy perspectives. Methanol synthesis from CO2 hydrogenation not only produces methanol which is a key platform chemical and a clean fuel, but can also recycle CO2 which is one of the major greenhouse gases causing global warming. As a mobile energy carrier (particularly as a hydrogen carrier), methanol is a versatile molecule which is able to generate H2 via its decomposition. Catalysis plays a decisive role in the success of both methanol synthesis from CO2 hydrogenation and its reverse decomposition reaction. Pd/Ga2O3 binary catalyst has recently been identified as an active catalyst for the methanol synthesis reaction. In this thesis, it is reported the shape effect of Pd promoted Ga2O3 for this reaction. The catalytic H2 evolution from methanol photodecomposition has also been studied over these catalysts. Three shapes of Ga2O 3 nanomaterials (i.e. rod and plate β-Ga2O3, and particle γ-Ga2O3) have been synthesized, followed by doping with Pd metal to form corresponding Pd/Ga2O3 nanocatalysts. It was found that a (002) polar Ga2O3 surface which was dominantly presented on the plate form was unstable, giving a higher degree of oxygen defects and mobile electrons in the conduction band than the other non-polar (111) and (110) surfaces of the rod form. It was shown that a significantly stronger metal support interaction was found between the (002) polar Ga2O3 on the plate form and Pd, which gave higher methanol yield and selectivity. For methanol photodecomposition, it was found that, for pure Ga2O3 catalysts of different shapes, the plate form with a highest degree of defects (unstable polar surface) could encourage a non-radiative catalytic recombination of electron and hole pairs upon irradiation, hence giving a highest photocatalytic activity for H2 production. Once Pd was introduced onto these oxide surfaces, it was noted that there was a fast and readily electron transfer from the conduction band of Ga2O3 to Pd due to the formation of a Schottky junction between the two materials. This produces metal sites for hydrogen production and further enhances the rate of the photocatalytic reaction over the radiative recombination of excitons. However, it was also found that at higher Pd content (>1%), the significantly shortened exciton lifetimes reduce the catalytic rate hence giving an overall volcanic response of activity to increasing Pd content for each shape of Ga2O3. At the higher Pd content, the plate form appeared to sustain a longer lifetime for photocatalysis compared to the other forms at the equivalent Pd loading.